2012
DOI: 10.1097/nmc.0b013e3182482c5e
|View full text |Cite
|
Sign up to set email alerts
|

Childbearing Depression and Childhood Aggression

Abstract: Introduction Childbearing depression (CBD) and childhood aggression are serious and international problems that encumber public health. Although maternal depression has received much attention in the literature in the last three decades, clinically it remains under-diagnosed and under-treated, especially during pregnancy. As a result, many mothers and families are left to suffer its long-lasting physical and psychosocial effects. This article's aim is to review the current literature on whether CBD increases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Four SRs reported on a variety of outcomes. One155 suggested that chronic maternal depression may play an important role in a child being overweight while another156 reported that when maternal depression exists, early childhood aggression is more likely to occur. Parental prenatal and postnatal depression was found to be responsible for increasing the mean rate of behavioural and emotional problems157 and antenatal depression was found to affect children’s conduct problems and antisocial behaviours 158…”
Section: Resultsmentioning
confidence: 99%
“…Four SRs reported on a variety of outcomes. One155 suggested that chronic maternal depression may play an important role in a child being overweight while another156 reported that when maternal depression exists, early childhood aggression is more likely to occur. Parental prenatal and postnatal depression was found to be responsible for increasing the mean rate of behavioural and emotional problems157 and antenatal depression was found to affect children’s conduct problems and antisocial behaviours 158…”
Section: Resultsmentioning
confidence: 99%
“…For example, aggression level may affect the decision to initiate or increase medication dosage in pediatric ADHD treatment [ 36 ]. Regardless of the controversy over whether to consider impulsive aggression as an independent categorical diagnosis like a disorder [ 37 ] or a measurable symptom secondary to some other diagnostic entity like fever or pain [ 32 , 38 ], it can greatly impact an individual’s development and health, or even lead to high economic and medical burden for families and communities [ 39 - 41 ]. This paper does not aim to address the dispute over the clinical perception of aggression by joining any side or to unduly correlate 16p13.11 microduplication with the aggression phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Untreated postpartum depression can have effects on infants’ wellbeing into adolescence, including poor cognitive functioning, violent behavior, and externalizing disorders [ 7 ]. Further, young children of depressed mothers have been found to exhibit more fussiness and aggression relative to young children of healthy mothers [ 1 , 8 ]. Behavioral problems in young children, particularly boys, are also specifically tied to paternal depression beyond the effects seen from maternal depression [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%